Aesthetic value from a philosophical perspective in the environmental biomonitoring of heavy metal pollution in aquatic ecosystems - Argota-Pérez, George (2024)
Th e study aimed to describe the aesthetic value from a philosophical perspective in environmental biomonitoring of heavy metal pollution in aquatic ecosystems. Conducted between March and August 2023, the study focused on assessing aesthetics in this context. Aesthetic appreciation, aesthetic disturbance, and aesthetic integration were considered primary dimensions along with their respective indicators. It was emphasized that aesthetic appreciation in biomonitoring of heavy metal pollution highlights the importance of considering visual beauty and its relationship with environmental health. From a philosophical standpoint, this aesthetic assessment refl ects the ecosystem’s harmony and vitality. Aesthetic disturbance signals alterations in this harmony, indicating signifi cant value losses. Integrating aesthetics into monitoring programs not only protects the environment’s beauty but also reflects an ethical responsibility towards nature. It is underscored that the aesthetic value in environmental biomonitoring of heavy metal pollution in aquatic ecosystems emphasizes the connection between visual beauty and ecosystem health. It reflects deeper aspects of harmony, integrity, and vitality, not solely subjective perception but also objective indicators of environmental health. Recognizing and preserving this aesthetic value guides ethical action and promotes conservation efforts. In conclusion, aesthetics in environmental biomonitoring of heavy metals highlights the link between beauty and environmental health, fostering ethical conservation.